Dish composition: children's mental representation and expected liking. Issue 9 (7th September 2015) - Olsen, Nina Veflen; Altintzoglou, Themistoklis; Almli, Valérie Lengard; Hersleth, Margrethe; Skuland, Aase; Honkanen, Pirjo
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to investigate how vegetable side components (carrot and broccoli) influence children's associations and expected liking of two common Norwegian dishes (meatballs and salmon). Design/methodology/approach – Children aged 11-12 years old were recruited to complete an adapted free association test (n=89). Each participant was exposed to four pictures of dishes that included combinations of the experimental food items served with potatoes and sauce. Participants stated their immediate associations and how much they liked each meal on a five-point smiley face scale for children. Evoked associations were coded and categorized before the relationship between the expected liking of the dishes and the associations were visualized based on correspondence analysis. Findings – The authors found that the expected liking of the dishes was significantly affected by the composition of the dish, that the associations related to the meal changed when the vegetable component changed, and that children's associations to food are quite similar to what previous studies have found for adults. Originality/value – How children categorize complex dishes and how their mental representation explains expected liking has rarely been investigated before. By investigating how dishes with different components activate different associations and how these associations co-occur with children's expected liking of the dishes, the authors gain knowledge that can help us develop strategies for improved dietary change.